2011
DOI: 10.1088/0957-4484/22/31/315201
|View full text |Cite
|
Sign up to set email alerts
|

A multi-level capacitor-less memory cell fabricated on a nano-scale strained silicon-on-insulator

Abstract: A multi-level capacitor-less memory cell was fabricated with a fully depleted n-metal-oxide-semiconductor field-effect transistor on a nano-scale strained silicon channel on insulator (FD sSOI n-MOSFET). The 0.73% biaxial tensile strain in the silicon channel of the FD sSOI n-MOSFET enhanced the effective electron mobility to ∼ 1.7 times that with an unstrained silicon channel. This thereby enables both front- and back-gate cell operations, demonstrating eight-level volatile memory-cell operation with a 1 ms r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…To overcome the scaling-down limit beyond the DRAM cell design rule of less than 10 nm, a capacitor-less memory cell, called a 1-transistor (1T)-DRAM, has been proposed. Note that a 1T-DRAM can perform DRAM cell operations by utilizing the kink effect for a fully depleted silicon-on-insulator (FD SOI) n-MOSFET [14]. The feasibility of a 1T-DRAM satisfying the memory cell design rule of less than 10 nm has been demonstrated by the nonnecessity of a selector and a simple capacitor structure and suggests the possibility of multi-level cell operation.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the scaling-down limit beyond the DRAM cell design rule of less than 10 nm, a capacitor-less memory cell, called a 1-transistor (1T)-DRAM, has been proposed. Note that a 1T-DRAM can perform DRAM cell operations by utilizing the kink effect for a fully depleted silicon-on-insulator (FD SOI) n-MOSFET [14]. The feasibility of a 1T-DRAM satisfying the memory cell design rule of less than 10 nm has been demonstrated by the nonnecessity of a selector and a simple capacitor structure and suggests the possibility of multi-level cell operation.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the one transistor (T)-DRAM, fabricated with a fully depleted silicon-on-insulator (FDSOI) n-MOSFET and three electrodes (i.e. gate, source, and drain), has been proposed [8][9][10][11]. However, it also faces the scaling-down issue of an FDSOI n-MOSFET similar to an n-MOSFET of the DRAM cells because it has a fundamental memory cell size of 6F 2 , which cannot be reduced to 4F 2 (F represents the minimum feature size).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that scaling-down below the half-pitch size of 20 nm would be the physical limit of the conventional memory cell structure, consisting of one n-metal-oxide-semiconductor field-effect transistor (n-MOSFET) and one cylindrical capacitor, because the capacitors of the DRAM cells would collapse on one another [4][5][6][7][8]. The capacitor-less memory cell is a promising candidate to overcome the limitation of the conventional DRAM cell structure, being produced by just one n-MOSFET fabricated on a silicon-on-insulator (SOI) substrate and performing volatile memory cell operation [9][10][11]17]. Many research works improving the retention time (or memory margin) of capacitor-less memory cells have been reported [12][13][14]17].…”
Section: Introductionmentioning
confidence: 99%
“…The capacitor-less memory cell is a promising candidate to overcome the limitation of the conventional DRAM cell structure, being produced by just one n-MOSFET fabricated on a silicon-on-insulator (SOI) substrate and performing volatile memory cell operation [9][10][11]17]. Many research works improving the retention time (or memory margin) of capacitor-less memory cells have been reported [12][13][14]17]. In particular, it was reported that the insertion of a strained SiGe layer between the Si channel and the buried oxide layer for a capacitor-less memory cell fabricated on the unstrained Si channel on the strained SiGe layer-on-insulator (unstrained Si ε-SGOI capacitor-less memory cell) resulted in confining more holes at the source edge and enhancing the memory margin of the capacitor-less memory cell, although the electron mobility of the unstrained Si ε-SGOI capacitor-less memory cell was degraded by inserting a strained SiGe layer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation